2022
DOI: 10.3390/en15020463
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Upgrading of a Biodetergent for Application in the Industrial Energy Sector

Abstract: In the industries across the petroleum chain and those involved in energy generation, the use of petroderivatives as fuel oils is common. To clean parts, equipment and environments contaminated by hydrocarbons, they use expensive, toxic products, bringing risks to the environment as well as to workers’ health. Thus, the aim of this study was to check the stability of a biodetergent prepared using atoxic substances for large-scale production and industrial energy sector application. The relationship between vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
(61 reference statements)
0
2
0
Order By: Relevance
“…An ecological biodegreasing agent is non-toxic and environmentally compatible when present in soil, rivers, or marine environments. Such sustainability meets the demands of consumers for "greener" cleaning products [6,115].…”
Section: Application Of Biosurfactants In Degreasing Industrymentioning
confidence: 99%
“…An ecological biodegreasing agent is non-toxic and environmentally compatible when present in soil, rivers, or marine environments. Such sustainability meets the demands of consumers for "greener" cleaning products [6,115].…”
Section: Application Of Biosurfactants In Degreasing Industrymentioning
confidence: 99%
“…Few studies have shown the potential to incorporate microbial surfactants into highvalue bioproduct formulations for the detergent industry [13,14,18], particularly for use in the petroleum industry. The combination of biosurfactants with safe ingredients has also been very little explored.…”
Section: Introductionmentioning
confidence: 99%